2011
DOI: 10.1111/j.1600-9657.2011.01099.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for dental radiography immediately after a dento‐alveolar trauma, a systematic literature review

Abstract: –  The objective with this study was to search for and to analyze the presence of scientific papers, guidelines, and recommendations in dental literature regarding which radiographs should be prescribed after a dento‐alveolar trauma. We know from earlier that guidelines and recommendations are available in general in dental traumatology. The International Association of Dental Traumatology (IADT) has earlier developed guidelines for the management of dental trauma cases in general. There are also recommendatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 51 publications
(59 reference statements)
0
22
0
2
Order By: Relevance
“…It must be considered that the present study did not feature any cases of root or alveolar fractures. Radiographic examination is considered necessary for the diagnosis of these TDI categories, and the lack of these cases probably increased the mean levels of interexaminer agreement in the current study. The possibility of sharing radiographic images, which might aid the remote diagnosis of these traumas, must also be considered …”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…It must be considered that the present study did not feature any cases of root or alveolar fractures. Radiographic examination is considered necessary for the diagnosis of these TDI categories, and the lack of these cases probably increased the mean levels of interexaminer agreement in the current study. The possibility of sharing radiographic images, which might aid the remote diagnosis of these traumas, must also be considered …”
Section: Discussionmentioning
confidence: 83%
“…Radiographic analysis is always recommended in TDI cases, especially in cases of root and alveolar fractures, in which a clinical examination and diagnosis have limitations. Even so, a clinical evaluation is a necessary starting point as it determines the most adequate therapeutic technique and indicates which complementary radiographic examinations would be appropriate . Unfortunately, ideal conditions for the radiographic imaging of TDIs are not always available.…”
Section: Discussionmentioning
confidence: 99%
“…Figure illustrates how multiple radiographs at differing angulation can disclose lateral luxation. Many authors advocate the use of multiple films at different angulations to best identify intra‐alveolar root fractures , and indeed, this is the current IADT recommendation. Molina et al.…”
Section: Radiographic Techniquementioning
confidence: 99%
“…Kullman and Al Sane in a systematic review in 2012 reported a lack of evidence‐based research on radiographic methods although there was support for the current recommendations in the IADT guidelines. A PubMed search using the same search words for articles published since 2012 revealed no papers with specific recommendations on guidelines, while a number of articles advocated judicious use of CBCT when considered clinically appropriate .…”
Section: Radiographic Techniquementioning
confidence: 99%
See 1 more Smart Citation